Ptyctimous mites (Acari, Oribatida) from Southern Vietnam with descriptions of three new species - Niedbała, Wojciech; Ermilov, Sergey G. (Zootaxa, 2013)
An annotated checklist of ptyctimous mite taxa from Southern Vietnam, including 18 species, 11 genera and seven families, is provided. Three new species.—Apoplophora minuscula Niedbała sp. nov., Acrotritia proxima Niedbała sp. nov. and Sabahtritia dongnaiensis Niedbała sp. nov.—are described. Some remarks on descriptions of Vietnamese Apoplophora pantotrema (Berlese, 1913) and Arphthiracarus tubulus (Hammer, 1972) are presented.